2016
DOI: 10.1039/c6cp06168k
|View full text |Cite|
|
Sign up to set email alerts
|

Supramolecular influence on cis–trans isomerization probed by ion mobility spectrometry

Abstract: We used tandem ion mobility spectrometry measurements to investigate how the photo-isomerization of a chromophore (a methylpyridinium derivative) is affected by the complexation with a crown ether. A dramatic blue-shift of the photo-isomerization spectrum was observed upon complexation, which could be well reproduced by ab initio calculations. Our results support that the observed changes in the photo-physical properties of the chromophore originate from the charge-solvation of its pyridinium moiety by the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…As examples, a single water molecule was found to shift the absorption spectrum of the highly symmetric MnO 4 − ion by only 0.01 eV, while a shift of 0.2 eV was measured for the (intrinsic) CT‐transition of meta ‐nitrophenolate . Recent work by Dugourd and co‐workers also showed that a methylpyridinium derivative experiences a shift in absorption by 0.4 eV upon complexation with 18‐crown‐6 ether in agreement with the strong intrinsic CT character of the transition. Finally, beautiful evidence for the importance of the character of the excited state was reported by Jouvet and co‐workers: The absorption by protonated polycyclic aromatic hydrocarbons (PAHs) does not simply redshift with molecular size as it does for the neutral analogues.…”
Section: Figuresupporting
confidence: 84%
“…As examples, a single water molecule was found to shift the absorption spectrum of the highly symmetric MnO 4 − ion by only 0.01 eV, while a shift of 0.2 eV was measured for the (intrinsic) CT‐transition of meta ‐nitrophenolate . Recent work by Dugourd and co‐workers also showed that a methylpyridinium derivative experiences a shift in absorption by 0.4 eV upon complexation with 18‐crown‐6 ether in agreement with the strong intrinsic CT character of the transition. Finally, beautiful evidence for the importance of the character of the excited state was reported by Jouvet and co‐workers: The absorption by protonated polycyclic aromatic hydrocarbons (PAHs) does not simply redshift with molecular size as it does for the neutral analogues.…”
Section: Figuresupporting
confidence: 84%
“…[13] As examples,asingle water molecule was found to shift the absorption spectrum of the highly symmetric MnO 4 À ion by only 0.01 eV, [9] while as hift of 0.2 eV was measured for the (intrinsic) CT-transition of meta-nitrophenolate. [8] Recent work by Dugourd and co-workers [14] also showed that am ethylpyridinium derivative experiences as hift in absorption by 0.4 eV upon complexation with 18-crown-6 ether in agreement with the strong intrinsic CT character of the transition. Finally,b eautiful evidence for the importance of the character of the excited state was reported by Jouvet and co-workers: [15] Thea bsorption by protonated polycyclic aromatic hydrocarbons (PAHs) does not simply redshift with molecular size as it does for the neutral analogues.…”
mentioning
confidence: 79%
“…Our collaboration has also studied these proteins by means of IMS and IR spectroscopy . Recently, tandem IMS emerged as a technique allowing to select a conformer of a given molecular ion of controlled m / z ratio, activate it by low‐energy collisions or laser photoabsorption, and monitor the induced structural changes …”
Section: Figurementioning
confidence: 99%
“…[21] Recently,t andem IMS emerged as at echnique allowing to select ac onformer of ag iven molecular ion of controlled m/ z ratio, activate it by low-energy collisions or laser photoabsorption, and monitorthe induced structural changes. [22][23][24][25][26][27][28] In this work, we report the results of experiments using tandem IMS coupled to mass spectrometry,a pplied to the investigation of the structure ands tability of CMP in the gas phase, and give ad efinitive answer to the origin of the triple helix stabilization by hydroxyproline. Furthermore, we add insight into the requirementsf or triple-helical CMP self-assembly, which might shed light on collagen fibril growth.…”
mentioning
confidence: 99%